Seed morphology in the tribe Chloraeeae (Orchidaceae): combining traditional and geometric morphometrics - Chemisquy, Maria Amelia (2009)
Previous work on orchid seeds showed that characters associated with the seed coat may be useful for classification and phylogeny at a suprageneric level. Seed morphology of several species of the tribe Chloraeeae is analyzed using traditional morphometrics while seed shape is studied, for the first time, using tools of geometric morphometrics. Seed characters are evaluated by their discriminative power and the information they may provide in a phylogenetic context. Contrary to previous findings, seed shape resulted in a continuum among the taxa studied, and only in a few cases genera or groups of species could be discriminated based on shape. On the contrary, seed size, expressed as centroid size, was a variable character and informative at a phylogenetic level. Traditional measures of seed coat, mainly those of seed coat cells, were also helpful for discriminating genera and species, agreeing with previous statements about their utility in taxonomy and phylogeny.